Facile synthesis of nitrogen-doped carbon dots from COOH-functional ionic liquid and their sensing application in selective detection of free chlorine. (16th September 2016) - Wang, Congyue; Wang, Chunfeng; Sun, Dong; Li, Aoqi; Chen, Yujuan; Zhuo, Kelei
Abstract: Heteroatom doped carbon dots (CDs) possess many unique properties and have attracted increasing attention. The precursor is vital for the preparation of highly fluorescent heteroatom doped CDs. Herein, 1, 3-bis(carboxymethyl)imidazolium chloride ([Im(AH)2 ]Cl, a COOH-functional ionic liquid) and aminoethylethanolamine (AEEA) were firstly used as precursors to prepare nitrogen-doped carbon dots (N-CDs) by a simple one-step pyrolysis approach. The effects of reaction time, temperature, and mass ratio of precursors on the quantum yield (QY) of N-CDs were investigated. The prepared N-CDs are spherical morphology with an average diameter of 2.4 nm, and have blue fluorescence with a QY of 23.2% and excitation-dependent emission behavior. They also possess good water solubility and fluorescent stability. In addition, based on the obtained N-CDs, a sensing method of free chlorine detection in acidic water system was introduced. The proposed method has good sensitivity and selectivity to free chlorine, and exhibits a nice linear response in the concentration range from 0.2 to 22 μ M with a detection limit of 0.15 μ M. Furthermore, this sensing method was successfully applied to detect free chlorine of tap water with satisfactory recovery (97%–103%), suggesting it has the potential application in water quality monitoring.